2019
DOI: 10.3168/jds.2019-16311
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of the clostridial load in the teats of lactating cows with lysozyme derived from donkey milk

Abstract: The use of a sterilized product for washing cows' udders before milking may be useful to reduce or prevent Clostridium tyrobutyricum contamination, the main cause of the late-blowing defect in hard and semi-hard cheeses. The aim of this research was to evaluate the antibacterial efficacy of an experimental formula containing 15% condensed donkey milk (lysozyme content 825 mg/L). The antimicrobial activity of condensed milk was first evaluated in vitro, using the disk diffusion method, on the following microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The antimicrobial activity of condensed milk was firstly evaluated in vitro, using the disk diffusion method on the following microorganisms: Bacillus megaterium , Bacillus mojavensis , Clavibacter michiganensis , and Clostridium tyrobutyricum . These tests were compared with the effects of two antibiotics, ampicillin (100 mg/mL) and kanamycin (50 mg/mL), and a commercial pre-dipping formula, showing that the inhibitory activity of lysozyme from donkey milk on all the considered microorganisms was higher than that of the commercial product and similar to that of the two antibiotics [ 215 ]. Bovine viral diarrhea virus (BVDV), an enveloped, single-stranded, positive-sense RNA virus from the Flaviviridae family, is a globally distributed bovine pathogen.…”
Section: Applications Of Lysozymementioning
confidence: 99%
“…The antimicrobial activity of condensed milk was firstly evaluated in vitro, using the disk diffusion method on the following microorganisms: Bacillus megaterium , Bacillus mojavensis , Clavibacter michiganensis , and Clostridium tyrobutyricum . These tests were compared with the effects of two antibiotics, ampicillin (100 mg/mL) and kanamycin (50 mg/mL), and a commercial pre-dipping formula, showing that the inhibitory activity of lysozyme from donkey milk on all the considered microorganisms was higher than that of the commercial product and similar to that of the two antibiotics [ 215 ]. Bovine viral diarrhea virus (BVDV), an enveloped, single-stranded, positive-sense RNA virus from the Flaviviridae family, is a globally distributed bovine pathogen.…”
Section: Applications Of Lysozymementioning
confidence: 99%
“…In fact, the modifications in the amount of these different cell populations in milk according to the udder health conditions relates to the actual inflammatory status of the mammary glands [11,12]. Moreover, there is evidence that different proportions of these cell populations, within specific SCC levels, could modify the final characteristic of dairy products [13,14], as well as different categories of environmental microorganisms (i.e., Clostridia) that, although nonpathogenic, have a strong unfavorable dairy activity [15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interest in donkey milk has increased dramatically over the past few years due to its nutritional, nutraceutical, functional, and immunological properties (Aspri et al, 2017b). Several studies have demonstrated that donkey milk maintains antimicrobial (Zhang et al, 2008;Brumini et al, 2013;Koutb, 2016;Adduci et al, 2019), antiinflammatory (Jirillo and Magrone, 2014;Yvon et al, 2018), antimitotic, as well as antitumor (Mao et al, 2009) capacities. Furthermore, it has been reported to be a suitable alternative for infants suffering from cow milk protein allergy (Souroullas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%